Peran Budaya Sekolah dalam meningkatkan Kompetensi 4C Siswa - Marta Amalia Iflahah; Syunu Trihantoyo; Muhamad Sholeh; Amrozi Khamidi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to explore the role of school culture in enhancing 4C competencies (Critical Thinking, Creativity, Communication, Collaboration) among students in the era of globalization. Using a qualitative approach and a case study method, this research observes and analyzes school cultures in several institutions that implement a competency-based 4C approach. The findings indicate that a positive school culture, supported by visionary leadership, clear norms, and a conducive learning environment, can develop students who are not only intellectually capable but also possess strong character, discipline, and effective collaboration skills. This study also highlights the importance of teacher, parent, and community involvement in fostering a school culture that supports the development of 4C competencies. In this context, school culture is seen as a fundamental foundation in shaping an ideal learning environment where students feel safe, motivated, and willing to take risks to develop their potential. The study finds that schools with a strong culture can create spaces where critical thinking, creativity, communication, and collaboration are not only taught but also practiced in everyday life. Through in-depth observations, interviews, and document analysis, this research identifies key elements of an effective school culture, including the school's vision and mission, values and beliefs, norms and rules, rituals and traditions, communication patterns, physical environment, community relationships, and leadership.  Keywords : School Culture, 4C Competencies, Students